BOWMAN V. MONSANTO CASE: THE EUROPEAN PERSPECTIVE - Lazauskaite, Ruta (European Scientific Journal, ESJ, 2014)
The aim of this paper is to analyse the US Supreme Court’s decision in the Bowman v. Monsanto case, examine the arguments of the parties and assess their validity under European legislation and compare it with the US legal regulation. This paper also discusses particularities of patent and plant variety rights systems’ regulations, their historical origins and evolution, as well as interrelation between these two systems of biological material protection in the field of agriculture.With regard to the analysis of the US and European legislation it is concluded that despite some differences in the regulation of the patent protection in the field of biological matter, even if the Bowman v. Monsanto case had been examined in Europe, the final decision of the European court would not differ from the judgment of the US Supreme Court.